2014
DOI: 10.1177/1094670514539567
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Customers to Adhere to Expert Advice in Professional Services

Abstract: This study focuses on the mechanisms by which professional service providers effectively influence customers to adhere to their expert guidance and advice. Eliciting customer adherence is a critical concern for professional service firms since customers of these need-based (rather than want-based) services are often reluctant to adhere, and nonadherence can result in serious negative consequences to customer well-being and firm resource utilization. The study examines this scenario by developing a conceptual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
137
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(145 citation statements)
references
References 87 publications
1
137
0
7
Order By: Relevance
“…However, it has also been found that the degree to which the individual customer complies with and manages their illness is related to their mental view of how severe their situation is (Alogna 1980). This is supported by Seiders et al (2015), who found that focusing on negative consequences during medical consultations increased customer compliance with treatment. Therefore, even if the motivation is not internal, the customer's perception of how severe their situation is, in combination with direct consequences, is likely to have a positive impact on their motivation.…”
Section: Motivationmentioning
confidence: 97%
See 2 more Smart Citations
“…However, it has also been found that the degree to which the individual customer complies with and manages their illness is related to their mental view of how severe their situation is (Alogna 1980). This is supported by Seiders et al (2015), who found that focusing on negative consequences during medical consultations increased customer compliance with treatment. Therefore, even if the motivation is not internal, the customer's perception of how severe their situation is, in combination with direct consequences, is likely to have a positive impact on their motivation.…”
Section: Motivationmentioning
confidence: 97%
“…Several studies have suggested that elements connected to the specific environment influence health care customer practices (e.g., De Greef et al 2011;Varekamp, Verbeek, and van Dijk 2006;Seiders et al 2015). For example, De Greef et al (2011) found that physical environment features such as walkability, training equipment, and environmental aesthetics influence physical activity among persons with diabetes.…”
Section: Environmental Influencersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been varied research in the services marketing literature predominantly from the perspective of the customer, spanning the motivation of customers to adhere to expertise of clinicians in medical contexts (Seiders, Godfrey Flynn, Berry and Haws, 2015), looking into customers' experiences of failure in high-risk service settings (Tuncay Zayer, Otnes, and Fischer, 2015) and how customers can co-produce value in medication compliance with clinicians (Spanjol, Cui, Nakata, Sharp, Crawford, Xiao and Watson-Manheim, 2015). Fewer studies have examined the health care services contexts from the perspective of the service provider, save for a few notable exceptions (see Dagger et al, 2013;Day, Sinha and Thirumalai, 2013;Meyer Goldstein and Ward, 2004).…”
Section: Contributions To the Services Marketing Literature: On Separmentioning
confidence: 99%
“…Although personal information remains at the heart of personalised nutrition, the information exchange process suggests that service attributes such as communication mode, service scope, and service frequency also contribute to consumers intention to adopt personalised nutrition. Consumers may for instance be reluctant to disclose DNA to a service provider that limits himself to email communication (Metzger, 2004) or perceive information disclosure as more valuable when nutrition advice is provided more than once (Seiders, Flynn, Berry, & Haws, 2014). Since consumers' preference for and reaction to service attributes may differ from country to country (Pullman, Verma, & Goodale, 2001), to consolidate widespread adoption of 74 personalised nutrition it is important to identify which service attributes amplify or mitigate adoption intention across different countries.…”
mentioning
confidence: 99%